Evaluation of an Electrochemical Point‐of‐Care Meter for Measuring Glucose Concentration in Blood from Periparturient Dairy Cattle. (20th October 2015) - Megahed, A.A.; Hiew, M.W.H.; Townsend, J.R.; Messick, J.B.; Constable, P.D.
Abstract : Background: The Precision Xtra ® meter is a promising low cost electrochemical point‐of‐care unit for measuring blood glucose concentration ([gluc]) in cattle blood. The meter uses an algorithm that assumes the intra‐erythrocyte [gluc] equals the plasma [gluc] on a molal basis, and that the hematocrit is similar in humans and cattle. Objectives: The primary objective was to determine the accuracy of the meter for measuring plasma [gluc] in dairy cattle. Secondary objectives were to characterize the influence of hematocrit and sample temperature on the measured value for [gluc]. Animals: A total of 106 periparturient Holstein‐Friesian cattle. Methods: Blood and plasma samples (1, 109) were obtained and Deming regression and Bland–Altman plots were used to determine the accuracy of the meter against the reference method (plasma hexokinase assay). Multivariable regression and linear regression were used to determine the effect of hematocrit and sample temperature on the plasma [gluc] measured by the meter. Results: Intra‐erythrocyte [gluc] was 18% of plasma [gluc] on a molar basis. Sample temperature had a significant linear effect on plasma [gluc] as measured by the meter for 3/5 plasma samples when measured [gluc] > 160 mg/dL. Conclusions and clinical importance: The meter utilizes an algorithm that is optimized for human blood and is inaccurate when applied to bovine blood. Until a cattle‐specific algorithm is developed, we recommend using plasma as the analyte instead of blood and calculating plasma [gluc] using the equation: [gluc] = 0.66 × [gluc]p‐meter + 15, where [gluc]p‐meter is the value reported by the meter. If blood is measured, then we recommend using the equation: [gluc] = 0.90 × [gluc]b‐meter + 15.